DEVELOPING MOBILE BASED AUTHENTIC LISTENING MATERIALS FOR SENIOR HIGH SCHOOL STUDENTS - M. Zaim; Refnaldi Refnaldi; Elsa Elfiona (Ta'dib, 2020)
Using technology in teaching and learning process has become a must in this era, because it facilitates the teachers and students to be connected to the learning materials. The purposes of this research were to develop mobile-based authentic listening materials and to find out the validity and practicality of the developed product. This is a research and development study that followed the ADDIE model. The respondents of the research were the tenth-grade students of SMA Pembangunan Padang. The instruments of this research were need analysis questionnaire, validation sheet, evaluation sheet, and practicality sheet. The results of the study were (1) The listening materials needed by the students and teachers were identified. The authentic listening materials were developed using the android application with Adobe Animate CC 2019 and were validated by two experts in English language teaching and one expert in media development. (2) The developed listening material was valid and practical both by the English language experts and the Media Development expert. Therefore, the developed product is appropriate to be used by the students and teachers as supplementary media in teaching and learning listening skill.